UNVEILING IDEOLOGY IN FOLKLORE: A CRITICAL DISCOURSE ANALYSIS OF THE TIMUN MAS AND BUTO IJO SCRAPBOOK THROUGH FAIRCLOUGH’S FRAMEWORK - Andayani, Wuwuh; Zuriyati; Anwar, Miftahulkhairah; Chaerunisyah, Ana (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2025)
This study aims to uncover the ideology embedded in the folk tale scrapbook of Timun Mas and Buto Ijo through the Critical Discourse Analysis (CDA) approach based on Norman Fairclough's model. Folk tales, as a form of cultural narrative, not only convey moral messages but also represent social constructions, power relations, and ideological values that exist within society. Using Fairclough's three-dimensional analysis (text, discourse practice, and social practice), this research explores how the visuals and narrative in the scrapbook reflect and reproduce certain ideologies, such as the relationship between power and bravery, the representation of female characters, and moral antagonism. The analysis results show that the text structure and visual elements in the scrapbook contribute to a re-interpretation of gender roles, power dominance, and resistance through the symbolism of the Timun Mas character. This study emphasizes the importance of a critical reading of culture-based learning media in revealing the hidden ideologies that shape the way young people think. Keywords: Critical Discourse Analysis, Folk Tale, Fairclough, Ideology, scrapbook, Timun Mas